Improving Learning Outcomes through Learning Media in Making Financial Reports at the Hospitality Board - Sulindawati, Ni Luh Gede Erni (Journal of Education Reseach and Evaluation, 2021)
Inadequate learning media used in hospitality accounting learning has an impact on the difficulty of understanding the learning material. This study examines the effectiveness of learning media in making hospitality financial reports through a spreadsheet application. The research design in this activity will use the development of learning tools, according to Sugiono. This research method uses a learning media development model which includes steps, namely product testing, product revision, and uses trials. The research subjects were students of the hospitality accounting study program. The instrument used consisted of observation guidelines, interviews, questionnaires, and learning outcomes tests. The participants of the product trial were 15 students of programming courses in hospitality accounting, and 34 people in one class were tested for use. The data analysis technique used in this research is descriptive by measuring the results of student learning tests seen from the scores obtained by students in learning the financial statements of hospitality companies. The assessment is carried out based on the scores obtained from the learning outcomes of attitude and participation assessment, assignment of assignments, and an assessment of the resulting product. The results of the evaluation of the use of media in making financial reports through spreadsheets show that student learning outcomes are excellent so that this media meets the requirements for the effectiveness of media learning so that this media can be used in educational accounting learning.